Examining the Impact of Strategic Leadership and Organizational Culture on Organizational Performance Considering the Mediating Role of Organizational Innovation (Case Study: Iran Khodro Company) - Borhan Ashkevari, Siavash (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study aims to investigate the effects of strategic leadership and organizational culture on organizational performance, with a focus on the mediating role of organizational innovation. Methodology: A descriptive-correlational research design was employed, utilizing structural equation modeling (SEM) based on partial least squares (PLS). Data were collected from 190 managers and experts at Iran Khodro Company using standardized questionnaires. The validity and reliability of the instruments were confirmed through Cronbach’s alpha, composite reliability, and average variance extracted (AVE). Findings: The results showed that both strategic leadership and organizational culture have significant positive effects on organizational performance and organizational innovation. Organizational innovation also positively impacts performance and mediates the relationships between strategic leadership and performance, as well as between culture and performance. Conclusion: Strategic leadership and organizational culture are critical drivers of organizational performance, and their effects are significantly enhanced through organizational innovation. These findings underscore the importance of fostering innovation as a mediating mechanism to improve performance outcomes in dynamic business environments.